2022
DOI: 10.3390/curroncol29020037
|View full text |Cite
|
Sign up to set email alerts
|

Case Report of Small Cell Carcinoma of the Ovary, Hypercalcemic Type (Ovarian Rhabdoid Tumor) with SMARCB1 Mutation: A Literature Review of a Rare and Aggressive Condition

Abstract: Small cell carcinoma of the ovary, hypercalcemic type (SCCOHT) is a rare and aggressive condition that is associated with the SMARCA4 mutation and has a dismal prognosis. It is generally diagnosed in young women. Here, we report a case of a young woman with SCCOHT harboring a rare molecular finding with a highly aggressive biological behavior. The patient had a somatic SMARCB1 mutation instead of an expected SMARCA4 alteration. Even though the patient was treated with high-dose chemotherapy followed by stem ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…SMARCA4 has both somatic and germline mutations, with germline variants showing up in anywhere between 8% and almost 40% of instances, depending on the cohort [ 5–7 ]. Later, a thorough genomic analysis of SCCOHT demonstrated that these tumors had an astonishingly low number of somatic mutations and genomic stability, bolstering the idea that epigenetic dysregulation is primarily responsible for these tumors’ occurrence [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SMARCA4 has both somatic and germline mutations, with germline variants showing up in anywhere between 8% and almost 40% of instances, depending on the cohort [ 5–7 ]. Later, a thorough genomic analysis of SCCOHT demonstrated that these tumors had an astonishingly low number of somatic mutations and genomic stability, bolstering the idea that epigenetic dysregulation is primarily responsible for these tumors’ occurrence [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The evidence that is now available, however, is made up of case reports or brief retrospective series with various management approaches, because no randomized studies have been done so far. A multicenter phase II trial at Institut Gustave Roussy is the only prospective clinical study in SCCOHT that tested a combination chemotherapy (PAVEP: cisplatin, adriamycin, vepeside, and cyclophosphamide) followed by radical surgery, high dose chemotherapy, and autologous stem cell transplant, and found that among the 27 SCCOHT patients, the 3-year survival rate was 49% [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fourteen articles provided suggestions for targeted therapies [2,11,34,42,60,64,65,71,73,[75][76][77][78]. The majority of the articles discussed the promising results from mainly preclinical studies.…”
Section: Potential Targeted Therapiesmentioning
confidence: 99%
“…Small cell carcinoma of the ovary, hypercalcemic type (SCCOHT) is a very rare (<0.01% of ovarian malignancies) and highly malignant ovarian cancer that predominantly affects young women [ 1 ]. The mean age of diagnosis is 23 years and the long-term survival rate in early-stage cases is around 30%, with the majority of patients dying within two years of diagnosis [ 1 , 2 ]. There are fewer than 500 reported cases of SCCOHT in the current literature and an established treatment regimen for the malignancy does not currently exist [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%